Application of using Hybrid Renewable Energy in Saudi Arabia - Al-Ammar, E. A.; Malik, N. H.; Usman, M. (Engineering, Technology & Applied Science Research, 2011)
One of the major world wide concerns of the utilities is to reduce the emissions from traditional power plants by using renewable energy and to reduce the high cost of supplying electricity to remote areas. Hybrid power systems can provide a good solution for such problems because they integrate renewable energy along with the traditional power plants. In Kingdom of Saudi Arabia a remote village called Al-Qtqt, was selected as a case study in order to investigate the ability to use a hybrid power system to provide the village with its needs of electricity. The simulation of this hybrid power system was done using HOMER software.